Ideological perspectives on the dynamics of code-switching in the business domain - Valdez, Paolo Niño M. (2009)
Through the years, advances in bilingual research has led scholars to believe that code-switching (CS) is more than a systematic, rule-governed behavior. However, attempts at formulating a data-driven model that incorporates aspects of culture have been deemed problematic due to theoretical and methodological issues concerning the determination of particular aspects of culture that need to be analyzed in bilingual interaction. This paper revisits the dynamics of code-switching in the business domain. An extension of interactional sociolinguistics, this investigation employs the use of ideological analysis in order to describe the role of CS in interactions in the business domain. It proceeds with an examination of apparent ideologies in selected communicative situations in the aforementioned domain. The findings of the study suggest that code-switching in business transactions is governed by ideology as manifestation of power. In addition, this paper concludes with possible implications for studying bilingual behavior in the context of different domains.
Includes bibliographical references (pages 43-46).